Trade-off entre crescer, reproduzir e defender: uma análise experimental do barbatimão e os insetos associados aos seus frutos - Mendes, Juliana Tuller (2017)
Plant phenology and plant investment in leaf biomass, reproduction, and defense are influenced by biotic and abiotic effects. Fertilizer application and leaf removal may change nutrient availability, and, in consequence, alter the resource quantity and n for herbivorous insetcs and their parasitoids. A two-way crossed experimental design was performed by fertilizer addition in the soil and 100% of leaf removal and tested the hypotheses that i) fertilization positively influences plant reproduction, and defoliation negatively influences it, and that defoliation alters leaf replacement time; ii) harvesting leaves of Stryphnodendron adstringens, as a source of tannin, would negatively affect plant investment in vegetative biomass and reproduction, and increase tannin concentrations in plant's tissues, and that fertilization would ameliorate the effects of leaf harvest; and iii) fertilization positively influences resource quantity and nutritional quality, while leaf removal positively influences chemical compounds production, since the fertilization positively impact fruit-associated insects and leaf removal negatively impact them. Vegetative investment was determined by total leaf biomass, reproduction by inflorescence and fruit production traits, and defense by total phenol, hydrolyzable tannin, and condensed tannin amount. Total protein, carbohydrates and lipids in fruits were determined as resource nutritional quality; and number and size of seeds, and fruit biomass as resource quantity. Although all plants flowered, clipped plants produced only a few or no fruits. Defoliation altered leaf replacement time, since it occurred right after being clipped, assynchronously to control plants. In contrast, fertilization did not impact plant phenology, reproduction and defense, but it had a marginal positive effect on vegetative investment. We found high tannin amounts in leaves of S. adstringens produced both prior to and subsequent to clipping, further suggesting that leaves could serve as a sustainable alternative source of tannin. We found 26 insect species associated with S. adstringens fruits and seeds and percentage of seed consumed varied among insect orders, which was higher for Lepidoptera, followed by Hymenoptera and Coleoptera. Fertilizer application did not fruit and seed traits or the fruit-associated insects. Defesa química was not important for the fruit-associated insects, and only resource quality positively influenced the rate predation by Hymenoptera. We found that resource quantity increased the percentage of seed consumed by Lepidoptera and by Coleoptera, the total insect abundance and richness and the seed-feeding insect abundance. In addition, the higher the seed-feeding insect richness and abundance, the higher their parasitoid richness and abundance. As such, resource traits affect S. adstringens seed-feeding insects differently, but most of the fruit-associated insect community is determined by resource quantity or quality.